OP0079 HPR NON-PHARMACOLOGICAL CARE IN SYSTEMIC SCLEROSIS: OPENING THE BLACK BOX. (June 2019) - Stöcker, Juliane; Spierings, Julia; Vonk, Madelon; Hoogen, Frank van den; Nijhuis-van der Sanden, M.W.G.; Staal, J.B.; Satink, Ton; van den Ende, C.H.M.; ,
Abstract : Background: Although health professional (HP) treatments are considered to be a corner stone in the management of systemic sclerosis (SSc), little is known about the referral process to and the content of non-pharmacological care in SSc. Objectives: To describe non-pharmacological care in SSc from the perspective of Dutch HPs, including referral reasons, diagnostic focus, interventions used and alignment in the communication between HPs and rheumatologists. Methods: Dutch HPs were invited through their SSc patients to complete an anonymous online survey provided by the Dutch ARCH (Arthritis Research and Collaboration Hub) working group. The survey comprised multiple response and open questions covering six topics: sociodemographic questions, referral reasons, diagnostic focus, treatment targets, interventions and the assessment of quality of communication between HPs and rheumatologists based on the Consumer Quality Index (CQI) (rheumatoid arthritis, version 2.0). Referral reasons and treatment targets were examined by means of open questions, and then linked to the ICF (International Classification of Functioning, Disability and Health) following the refined ICF Linking Rules (Cieza, 2016). Results: A total of 79 HPs, 65.8% women (N=52), with a mean age of 41.2 (SD=13.6) from 8 different professions completed the survey. Physiotherapists were the largest group represented (73%, N=58). All in all 133 different referral reasons were reported that yielded 58 different ICF codes, of which 70.7% (N = 41) could be linked to the ICF domain "body structures and functions". The reported interventions focus on body functions and structures, training of daily activities, education and advices and psychosocial interventions (Table 1). The quality of communication between HPs and rheumatologists as perceived by the HPs is shown in Table 2. Conclusion: The results of this study show clear discrepancies between referral reasons and applied interventions, visible in the clear focus on body functions and structures on one hand and the broad spectrum of applied interventions on the other hand. It is possible that HPs make a translation of the reasons given for referral to the needs of the individual patient. Viewed from this perspective, it is questionable whether the referrals by the rheumatologists are sufficiently targeted. Further, the results describe a suboptimal communication between rheumatologists and HPs that should be targeted in practice and further research. Reference: [1] Cieza, et al., (2016). Refinements of the ICF Linking Rules to strengthen their potential for establishing comparability of health information. Disability and rehabilitation, 1-10. Disclosure of Interests: Juliane Stöcker: None declared, Julia Spierings Grant/research support from: Boehringer Ingelheim, Madelon Vonk Grant/research support from: Madelon Vonk has received unrestricted research funds from Actelion and Therabel, Consultant for: Madelon Vonk was a consultant for Actelion, Boehringer-Ingelheim, Speakers bureau: Actelion, Boehringer-Ingelheim, Roche, Frank van den Hoogen: None declared, M.W.G. Nijhuis-van der Sanden: None declared, J.B. Staal: None declared, Ton Satink: None declared, C.H.M. van den Ende: None declared